Ảnh hưởng của một số yếu tố tới khả năng hấp phụ Cu2+ của vật liệu bọc chitosan - Hùng, Đào Phi; Anh, Trịnh Đức; Toàn, Cao Văn; Nam, Trương Thị; Thắng, Lê Bá; Phong, Dương Văn; Thu Thủy, Phạm Thị; Hường, Nguyễn Thị (Vietnam Journal of Chemistry, 2015)
The influence of several factors on the adsorption ability of ion Cu2+ was studied. The results showed that chitosan immobilized on variety materials by solution containing 1% chitosan in acid acetic obtained the most efficiency when the solution using immobilization of chitosan was neutralized and the materials (rice straw, bagasse and coir) were pretreated by NaOH. The chitosan immobilized on rice straw and sand had the most efficient ability adsorption ion Cu2+ to compare with others, the optimal mass ratio of chitosan/carrier-materials to prepare chitosan coating sand = 5/100 and chitosan coating rice straw = 9/100, the ability adsorption ion Cu2+ were 10.25 and 13.65 (mg/g), respectively.